2018
DOI: 10.1093/tas/txy108
|View full text |Cite
|
Sign up to set email alerts
|

Increased lysine: metabolizable energy ratio improves grower pig performance during a porcine reproductive and respiratory syndrome virus challenge

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) reduces grower pig performance. The amino acid (AA) requirements and lysine:metabolizable energy ratio (Lys:ME) of health-challenged pigs for optimum performance are poorly understood. Two experiments were conducted to evaluate the effect of increasing standardized ileal digestible (SID) Lys:ME (g SID Lys per Mcal ME) on growth performance during a PRRSV challenge. In Exp. 1, a total of 379 barrows (51.3 ± 0.3 kg body weight [BW]) were allotted to one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 23 publications
6
9
0
Order By: Relevance
“…It is well established that Lys is the first-limiting AA in healthy pigs, and to ensure that the targeted amount of Lys is being consumed by the pig, diets are formulated on a ratio of Lys to energy (i.e., g SID Lys:ME). Previous breakpoint analysis from our group ( Schweer et al, 2018a ) has reported that during both an experimental and natural PRRSV challenge, increasing SID Lys:ME 10% to 20% above NRC (2012) requirements resulted in improved growth performance and feed efficiency. This increase in Lys:ME is presumably accounting for the reduced feed and Lys intake ( Schweer et al, 2017 ), thus preserving lean tissue.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…It is well established that Lys is the first-limiting AA in healthy pigs, and to ensure that the targeted amount of Lys is being consumed by the pig, diets are formulated on a ratio of Lys to energy (i.e., g SID Lys:ME). Previous breakpoint analysis from our group ( Schweer et al, 2018a ) has reported that during both an experimental and natural PRRSV challenge, increasing SID Lys:ME 10% to 20% above NRC (2012) requirements resulted in improved growth performance and feed efficiency. This increase in Lys:ME is presumably accounting for the reduced feed and Lys intake ( Schweer et al, 2017 ), thus preserving lean tissue.…”
Section: Discussionmentioning
confidence: 82%
“…The differences in severity of this negative impact on growth performance is thought to be a result of pig age, viral strain, and PRRS viral clearance rates ( Murtaugh et al, 2002 ). In recent years, Rochell et al (2015) and Schweer et al, (2018a) have reported that dietary treatment can aid in improving growth performance and feed efficiency of pigs experiencing PRRSV challenge. In particular, Schweer et al (2018a) reported that increasing the dietary SID Lys:ME by 10% to 20% above NRC (2012) requirement in 25 to 50 kg pigs increased growth performance and feed efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations